INTEGRATED STRATEGIES FOR SUSTAINABLE DEVELOPMENT OF SMART CITIES - Chipriyanov, Mihail (E-Journal VFU, 2025)
This article reflects the results of a study on integrated strategies as a key approach for the sustainable development of smart cities. In a context of increased urbanization, traditional management models prove insufficient. Emphasis is placed on the integrated approach, which unites various fields—from resource integration to sustainable urban mobility, civic participation, and public-private partnerships. The main thesis is that the true potential of intelligent technologies is unlocked only through coordinated strategic planning. The analyzed approach creates synergy, optimizes resources, encourages innovation, and improves the quality of life. It is proven that integrated strategies are fundamental to transforming cities into more effective, sustainable, and competitive urban (eco)systems.